Heterocyclic Compounds: Pharmacology of Pyrazole Analogs From Rational Structural Considerations - Costa, Rafael Fernades; Turones, Larissa Córdova; Cavalcante, Keilah Valéria Naves; Rosa Júnior, Ismael Aureliano; Xavier, Carlos Henrique; Rosseto, Lucimar Pinheiro; Napolitano, Hamilton Barbosa; Castro, Patrícia Ferreira da Silva; Neto, Marcos Luiz Ferreira; Galvão, Gustavo Mota; Menegatti, Ricardo; Pedrino, Gustavo Rodrigues; et al. (Frontiers in Pharmacology, 2021)
Low quality of life and life-threatening conditions often demand pharmacological screening of lead compounds. A spectrum of pharmacological activities has been attributed to pyrazole analogs. The substitution, replacement, or removal of functional groups on pyrazole ring appears consistent with diverse molecular interactions, efficacy, and potency of these analogs. This mini-review explores cytotoxic, cytoprotective, antinociceptive, anti-inflammatory, and antidepressant activities of some pyrazole analogs to advance structure-related pharmacological profiles and rational design of new analogs. Numerous interactions of these derivatives at their targets could impact future research considerations and prospects while offering opportunities for optimizing therapeutic activity with fewer adverse effects.